2006
DOI: 10.1371/journal.pmed.0030254
|View full text |Cite
|
Sign up to set email alerts
|

Inflammatory Manifestations of Experimental Lymphatic Insufficiency

Abstract: BackgroundSustained lymph stagnation engenders a pathological response that is complex and not well characterized. Tissue inflammation in lymphedema may reflect either an active or passive consequence of impaired immune traffic.Methods and FindingsWe studied an experimental model of acute post-surgical lymphedema in the tails of female hairless, immunocompetent SKH-1 mice. We performed in vivo imaging of impaired immune traffic in experimental, murine acquired lymphatic insufficiency. We demonstrated impaired … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

14
195
0
2

Year Published

2007
2007
2018
2018

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 197 publications
(216 citation statements)
references
References 49 publications
14
195
0
2
Order By: Relevance
“…Therefore, the ALND model enables us to study the effects of lymph stasis without significant adipose deposition. In contrast, the mouse tail model used in this study enables us to analyze the effects of more profound lymphatic injury and adipose deposition, since we and others have previously shown that this treatment results in substantial subcutaneous adipose deposition and that this process is chronic lasting as long as 12 wk postop (4,11,32,33). Using a direct comparison of these models, we found that IL-6 expression, activation of its downstream mediator, and serum changes in IL-6 concentration occur to a more significant degree in the tail model as compared with the ALND model.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the ALND model enables us to study the effects of lymph stasis without significant adipose deposition. In contrast, the mouse tail model used in this study enables us to analyze the effects of more profound lymphatic injury and adipose deposition, since we and others have previously shown that this treatment results in substantial subcutaneous adipose deposition and that this process is chronic lasting as long as 12 wk postop (4,11,32,33). Using a direct comparison of these models, we found that IL-6 expression, activation of its downstream mediator, and serum changes in IL-6 concentration occur to a more significant degree in the tail model as compared with the ALND model.…”
Section: Discussionmentioning
confidence: 99%
“…An experimental model of acute postsurgical lymphedema in the tails of mice was set up, as described by Tabibiazar et al (2006) with some modifications. In brief, male ICR mice (28-38 g) were randomly divided into three groups: a drugtreatment group, a sham-operated control group and a control group.…”
Section: Animal Modelmentioning
confidence: 99%
“…Although several experimental animal models, including dog hindlimb (Han et al, 1985), rat hindlimb (Kanter et al, 1990) or rabbit ear (Szuba et al, 2002) have been used for the study of secondary lymphedema by disturbing lymphatic transport through the removal of a circumferential band of skin and subcutaneous tissue, a new mouse model of acquired lymphatic insufficiency, reported by Tabibiazar et al (2006), appears to be suited for molecular studies on this aspect. Therefore, in this study, we used a mouse lymphedema model to detect and identify the free radicals using electron spin resonance (ESR) and spin-trapping methods.…”
Section: Introductionmentioning
confidence: 99%
“…Tabibiazar et al induced lymphedema in an animal model using a mouse tail, and observed an increase in fibroblast cells, hyperkeratosis, edema in epidermis, and expanded lymphatics in the dermis and subdermis in mouse tail histological samples [7].…”
Section: Introductionmentioning
confidence: 99%